Important aspects of gender-based violence in conditions of armed conﬂict in Ukraine and police responses - Kachynska, M. O.; Качинська, М. О.; ORCID: http://orcid.org/0000-0002-7319-4470 (Науковий вісник Ужгородського національного університету. Серія: Право. – 2021. – Вип. 65. – С. 403–406, 2021)
The article is devoted to selected aspects of gender-based violence in the context of the armed conﬂict in Ukraineб and the police response to these cases. The author considers the international legal regulation of prevention and counteraction to gender-based violence in the conditions of armed conﬂicts. The provisions of UN Security Council Resolution №1325, adopted on 31 October 2000, and UN Security Council Resolution №1296, adopted on 19 April of the same year, were analyzed separately. It is noted that the risk group, which is the most vulnerable to genderbased, should include internally displaced persons. When this category of people changes their place of residence due to the armed conﬂict in eastern Ukraine, they need specialist help and support from the community they are moving to, and especially from government agencies, including the police. In most cases, a district police ofcer is a frst contact ofcer who has complete information about the population in their area of service, their needs and characteristics. That is why the author points to the leading role of the district police ofcer among other police services and divisions in the feld of timely detection of gender-based violence. The article develops an algorithm of actions for district police ofcers in case of detection of gender-based violence, which contains signs of a crime, reveals some aspects of proceedings in this category, as well as the use of coercive measures by police. The author considers the forms of interaction of a district ofcer with other state bodies of state power and local government, as well as the public in the feld of prevention and counteraction to gender-based violence. Проаналізовано деякі аспекти гендерно-обумовленого насильства в умовах збройного конфлікту в Україні та реагуванню поліції на ці випадки. Розглянуто міжнародно-правове регулювання попередження та протидії гендерно-обумовленому насильству в умовах збройних конфліктів. Звернуто увагу, що до групи ризику, яка є найбільш уразливою до гендерно-обумовленого слід віднести внутрішньо переміщених осіб. Коли означена категорія людей змінює місце свого проживання через збройний конфлікт на сході України, вони потребують особливої допомоги та підтримки від громади, до якої вони переїжджають, і особливо від державних органів, у тому числі від поліції. Розкрито алгоритм дій дільничних фіцерів поліції у випадку виявлення гендерно-обумовленого насильства, що містить ознаки злочину, розкрито окремі аспекти провадження у справах даної категорії, а також застосування заходів примусу поліцейськими. Досліджено форми взаємодії дільничного офіцера із іншими державним органами державної влади та місцевого смоврядування, а також громадськістю у сфері попередження та протидії гендерно-обумовленому насильству. Проанализированы некоторые аспекты гендерно-обусловленного насилия в условиях вооруженного конфликта в Украине и реагирования полиции на эти случаи. Рассмотрено международно-правовое регулирование предупреждения и противодействия гендерно-обусловленному насилию в условиях вооруженных конфликтов. Обращено внимание, что к группе риска, наиболее уязвимой к гендерно-обусловленному следует отнести внутренне перемещенных лиц. Когда указанная категория людей меняет место своего проживания из-за вооруженного конфликта на востоке Украины, она нуждаются в особой помощи и поддержке общины, к которой она переезжает и особенно от государственных органов, в том числе от полиции. Раскрыт алгоритм действий участковых офицеров полиции в случае выявления гендерно-обусловленного насилия, содержащего признаки преступления, раскрыты отдельные аспекты производства по делам данной категории, а также применение мер принуждения полицейскими. Исследованы формы взаимодействия участкового офицера с другими государственными органами государственной власти и местного самоуправления, а также общественностью в сфере предупреждения и противодействия гендерно-обусловленному насилию.
Важливі аспекти ґендерного насильства в умовах збройного конфлікту в Україні та реакція поліції
Kachynska, M. Important aspects of gender-based violence in conditions of armed conﬂict in Ukraine and police responses / Kachynska Maryana // Науковий вісник Ужгородського національного університету. Серія: Право. – 2021. – Вип. 65. – С. 403–406. - DOI https://doi.org/10.24144/2307-3322.2021.65.72.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; Национальная полиция Украины; National police of Ukraine; поліція; полиция; police; дільничний офіцер поліції; участковый офицер полиции; district police officer; гендерно-обумовлене насильство; гендерно-обусловленное насилие; gender-based violence; Кримінологія. Criminology. Криминология; насильство; насилие; violence; протидія насильству; противодействие насилию; counteraction to violence; потерпілі; потерпевшие; victims; збройний конфлікт; вооруженный конфликт; armed conflict; внутрішньо-переміщені особи; внутренне перемещенные лица; internally displaced persons; міжнародні доровори; международные дороворы; international agreements; правове регулювання; правовое регулирование; legal regulation